Static and Seismic Stability of a Slope Reinforced with Two Rows of Piles - Chekroun, Lokmane El Hakim; Boumechra, Nadir (Engineering, Technology & Applied Science Research, 2023)
The use of piles for slide stabilization is considered among the most important innovative reinforcement techniques. Piles have been successfully used in many situations to stabilize slopes or as parts of a stability improvement. Our case study is in the Tlemcen section. The left side of the roadway collapsed following the slide of the downstream side. Inclinometer readings showed signs of instability with a slip depth of about 9m near the motorway platform. The likely causes of the instability were the removal of the lower abutment of the embankment upstream of the road and the establishment of an earth deposit which overloaded the embankment and disrupted the flow of water downstream. The stabilization study is based on the installation of two rows of anti-slip piles. Stability analysis study was carried out under static and dynamic loads and highlights that this solution is advantageous and effective.